2001
DOI: 10.1080/714052769
|View full text |Cite
|
Sign up to set email alerts
|

The combination of computerized cardiotocography and amniotic fluid index for the prediction of neonatal acidemia at birth: a modified biophysical profile

Abstract: We suggest that the cCTG + AFI score may be of value in the prediction of neonatal acidemia and help in the management of third-trimester high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The authors recommended the combination of the NST and OCT as the best indirect method and suggested a direct measure of the metabolic parameters in IUGR fetuses with abnormal tests since the positive predictive value of indirect methods was still low. Piazze et al [18] suggested that the computerized CTG and amniotic fluid index (modified FBP) may be valuable in the prediction of neonatal academia and help in the management of third-trimester high-risk pregnancies. Cozmi et al [22] supported previous studies that were conducted in fetuses with idiopathic growth restriction, low birth weight and umbil-ical artery reversed flow, and absent ductus venosus or reversed flow are associated with an increased perinatal morbidity and mortality, but CTG is not significant in the prediction of perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recommended the combination of the NST and OCT as the best indirect method and suggested a direct measure of the metabolic parameters in IUGR fetuses with abnormal tests since the positive predictive value of indirect methods was still low. Piazze et al [18] suggested that the computerized CTG and amniotic fluid index (modified FBP) may be valuable in the prediction of neonatal academia and help in the management of third-trimester high-risk pregnancies. Cozmi et al [22] supported previous studies that were conducted in fetuses with idiopathic growth restriction, low birth weight and umbil-ical artery reversed flow, and absent ductus venosus or reversed flow are associated with an increased perinatal morbidity and mortality, but CTG is not significant in the prediction of perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…nonreactive) is usually further assessed by additional antenatal surveillance tests [15] . The variables of the FBP and Doppler variables were often compared with other methods of perinatal monitoring [3,[16][17][18][19] . Dubiel et al [16] compared the Doppler assessment of umbilical arterial blood flow and the NST, a component of the FBP, in 599 pregnant women with a decrease in fetal movements.…”
Section: Discussionmentioning
confidence: 99%